Social Support and Health Promotion Lifestyles of Rural Women - Marsha H. Adams; Andrea G. Bowden; Debra S. Humphrey; Linda B. McAdams (Rural Nurse Organization; Binghamton University, 2017)
Health promotion is presently receiving increased attention regarding the prominent role it plays in the health care arena. The purpose of the study is to ascertain if a relationship exists between social support and health promotion lifestyles of rural women. The organizing framework for the descriptive correlational study is Pender's (1996) revised Health Promotion Model. The study participants are 400 women whose names were obtained by a simple, random sampling of the voter registration list of a rural county in a southeastern state responding to questionnaires. Data was analyzed using descriptive and inferential statistics. The data strongly supported Pender's (1996) Health Promotion Model and the significant role that social support plays in promoting a healthy lifestyle. Recommendations for further research include examining the relationship of social support and health promotion lifestyles with rural non-Caucasian women, replication of the study using participants who live in rural counties farther from metropolitan areas, and intervention development which may further enhance social support and health promoting lifestyles. Keywords: health promotion, social support, rural women, healthy lifestyle, rural health, health promoting lifestyle, rural, health, health responsibility, healthy behaviors http://dx.doi.org/10.14574/ojrnhc.v1i1.501